Profile of Students’ Creative Thinking Ability Reviewed from Self-Confidence - Rusiyaningsih, Kartika; Gunawan, Gunawan; Subekti, Fitrianto Eko (Proceedings Series on Social Sciences & Humanities, 2025)
Creative thinking skills are students' ability to find ways or solutions that are unusual, unique, and have never been found by others in solving problems. This study aims to describe the ability to think creatively from the perspective of students' confidence. The research method used is qualitative descriptive with data collection techniques through, questionnaires, tests, and interviews. Questionnaires were used to divide the categories of student confidence, written tests were used to determine creative thinking skills in solving problems, and interviews were used to dig deep into information to obtain information related to problem solving. The subject of this study is grade VIII students of SMP N 1 Pekuncen. Subjects were grouped into three categories of confidence, namely high, medium, and low based on the results of the questionnaire, using the purposive sampling technique, two people were taken as subjects in each category. The material used is a two-variable linear equation system. Data analysis techniques include data reduction, data presentation, and conclusion drawn. The results of the study explained that: 1) students with high categories were able to find solutions appropriately and could write down many ways to solve problems; 2) students in the medium confidence category can write down many ways to solve problems but cannot find the right solution; 3) students with low confidence categories are not able to find the right solution and are unable to write down many ways to solve problems.